Role of metal-support interaction for atmospheric pressure CO2 hydrogenation over Pd/(Ti)-SBA-15 catalyst: effect of titanium composition on products selectivity - Soni, Yogita; Gupta, Sharad; Vinod, C. P. (Molecular Catalysis, 2021)
The potential role of metal-support interaction for tuning the product selectivity during atmospheric pressure CO2 hydrogenation has been demonstrated on Pd/(Ti)-SBA-15 catalyst. Highly dispersed Pd NPs on SBA-15 (Pd/ SBA-15) was synthesized and further modified with titanium of varying composition. Comparison of catalytic activity of Pd/Ti-SBA-15 with its counterparts (Pd/SBA-15 and Pd/TiO2) illustrated the significance of strong PdTi interface in this catalyst and its role in tuning the product selectivity of CO2 hydrogenation. The generation of an ample amount of oxygen vacancies in the Pd/Ti-SBA-15 catalyst with maximum metallic Pd sites in close vicinity of Ti is proposed to boost the CO2 hydrogenation activity.
Keywords: CO2 hydrogenation; Metal-support interaction; Modified deposition precipitation; oxygen vacancies; Titanosilicates